2013
DOI: 10.3109/01612840.2013.837123
|View full text |Cite
|
Sign up to set email alerts
|

It's the Anxiety: Facilitators and Inhibitors to Nursing Students’ Career Interests in Mental Health Nursing

Abstract: Increasing the rate of recruitment of nursing students into mental health nursing (MHN) is vital to long-term sustainability of health care system support for people diagnosed with mental illness. However MHN is not a popular career path; this raises questions about what attitudes and beliefs may divert or attract students to this specialisation. The current research involved a survey of undergraduate nursing students at a regional university in Australia to clarify the nature of relationships between attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 27 publications
(39 reference statements)
2
40
0
Order By: Relevance
“…If students feel less anxious, they may be more likely to establish an enhanced therapeutic relationship with the patient thus achieving the goals of improving patient outcomes and compliance with treatment. Additionally, there is a current and projected shortage of psychiatric mental health nurses, and numerous studies indicate that student anxiety surrounding mental illness leads to negative stereotypes of the mentally ill and less interest in pursuing mental health nursing as a future career (Holmes, 2006;Happell, et al, 2014;Happell & Gaskin, 2012;Happell & Gough, 2009). Incorporation of SP simulation experiences into the mental health nursing course may be one method of enhancing student confidence and recruiting RNs into this specialty.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…If students feel less anxious, they may be more likely to establish an enhanced therapeutic relationship with the patient thus achieving the goals of improving patient outcomes and compliance with treatment. Additionally, there is a current and projected shortage of psychiatric mental health nurses, and numerous studies indicate that student anxiety surrounding mental illness leads to negative stereotypes of the mentally ill and less interest in pursuing mental health nursing as a future career (Holmes, 2006;Happell, et al, 2014;Happell & Gaskin, 2012;Happell & Gough, 2009). Incorporation of SP simulation experiences into the mental health nursing course may be one method of enhancing student confidence and recruiting RNs into this specialty.…”
Section: Discussionmentioning
confidence: 97%
“…Research has consistently identified that undergraduate nursing students express fear, anxiety, and uncertainty regarding mental health nursing and interacting with individuals diagnosed with mental illness (Corrigan, Kuwabara, & O'Shaughnessy, 2009;Happell & Gough, 2007;Happell, Robins, & Gough, 2008;Stuhlmiller, 2005). Educators are encouraged to identify innovative educational approaches that effectively prepare students for the demands in mental health nursing, reduce student anxiety, and ultimately, promote a positive view of this specialty (Happell, Platania-Phung, Harris, & Bradshaw, 2014;Happell & Gaskin, 2012).…”
Section: Review Of the Literaturementioning
confidence: 97%
“…Nursing educators can apply the marketing principle to repositioning PMHN and emphasize the value of choosing a PMHN career. In particular, in this repositioning effort, lever aging integrated marketing communication (IMC) relies on two major themes: the value-added role of PMHN vis-à-vis consumer behavior and in media communication [37]. Through an IMC approach to repositioning PMHN, communicating with and managing new nursing students, keeping an ongoing dialogue with PMHN graduates, and utilizing feedback from PMHN students to shape the nursing specialty are the main efforts to emphasize.…”
Section: Page 4 Ofmentioning
confidence: 99%
“…4 Factors contributing to this situation have been identified as negative attitudes towards people with mental illnesses negative experiences students had in psychiatric clinics, stigma and fear in trainers and nurses regarding psychiatric patients. [1][2][3][4][5][6][7][8] In the literature, there are studies reporting that the view that individuals with mental illness are dangerous and unpredictable is widespread in the general population. 9,10 It has been shown that many mental health professionals display more negative attitudes towards people with mental illnesses than do other people in a community.…”
mentioning
confidence: 99%
“…15,16 Strengthening positive attitudes towards mental health in nursing education may contribute to the retention of nurses in this field. 4,8 It has been reported that exposure to theory and clinical experience in psychiatric nursing affect attitudes towards psychiatric patients positively, contribute to their career choices and increase their interest in mental health. 11.17,18 In another study, it was determined that final-year nursing students who took the mental health and psychiatric-nursing course displayed more positive attitudes towards psychiatric patients and mental diseases, that they comprehended the role of a psychiatric nurse adequately at the end of the training process, but that they did not want to work in psychiatric clinics because they were not able to observe the roles of psychiatric nursing during clinical practices.…”
mentioning
confidence: 99%